Raman Spectroscopy Can Distinguish Glyphosate-Susceptible and -Resistant Palmer Amaranth (Amaranthus palmeri) - Singh, Vijay; Dou, Tianyi; Krimmer, Mark; Singh, Shilpa; Humpal, Dillon; Payne, William Z.; Sanchez, Lee; Voronine, Dmitri V.; Prosvirin, Andrey; Scully, Marlan; Kurouski, Dmitry; Bagavathiannan, Muthukumar (Frontiers in Plant Science, 2021)
Non-judicious use of herbicides has led to a widespread evolution of herbicide resistance in various weed species including Palmer amaranth, one of the most aggressive and troublesome weeds in the US. Early detection of herbicide resistance in weed populations may help growers devise alternative management strategies before resistance spreads throughout the field. In this study, Raman spectroscopy was utilized as a rapid, non-destructive diagnostic tool to distinguish between three different glyphosate-resistant and four -susceptible Palmer amaranth populations. The glyphosate-resistant populations used in this study were 11-, 32-, and 36-fold more resistant compared to the susceptible standard. The 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) gene copy number for these resistant populations ranged from 86 to 116. We found that Raman spectroscopy could be used to differentiate herbicide-treated and non-treated susceptible populations based on changes in the intensity of vibrational bands at 1156, 1186 and 1525 cm-1 that originate from carotenoids. Partial Least Squares Discriminant Analysis (PLS-DA) model indicated that within one day of glyphosate treatment (D1), the average accuracy of detecting herbicide-treated and non-treated susceptible populations were 90% and 73.3%, respectively. We also found that glyphosate-resistant and -susceptible populations of Palmer amaranth can be easily detected with an accuracy of 84.7% and 71.9% respectively, as early as D1. There were relative differences in the concentration of carotenoids in plants with different resistance levels but these changes were not significant. The results of the study illustrate the utility of Raman spectra for evaluation of herbicide resistance and stress response in plants under field conditions.